A critical examination of electrical engineering curricula across three institutions in New Zealand - Shepstone, Nigel Mark (Curtin University, 2009)
This thesis examines the effect of the curriculum structure on the pass rate of engineering students in three types of institutions in New Zealand; namely, a polytech, a university of technology, and a university.The pass rate of engineering students has historically been low in all three of these types of institutions. This resulted in the main research question for this study: ‘Is the present engineering curriculum structure in New Zealand the most effective structure in which to prepare engineering graduates for work in the 21st century?’. In order to investigate this question the current curriculum at the above three types of institutions was examined. This examination was undertaken from a number of perspectives. First, the philosophy of an engineering education was determined to establish what exactly an engineering education is. This philosophy was then used to determine which material is legitimate to include in an engineering curriculum and which material should be left out. Second, theories of teaching and learning were examined to determine whether the engineering curriculum is being taught in the most effective way. Third, the theories of curriculum structure and development were studied to determine whether the engineering curriculum is structured in accordance with the latest ideas in curriculum design. Finally, conclusions were drawn about current curriculum structure and whether it complies with modern pedagogical theory.The two main conclusions that were produced by this study are the following: • Engineering curricula are designed with almost no regard for the students that are required to undertake them. This is probably the major reason for the high failure rate. • Understanding in general and engineering understanding in particular are concepts that are not well understood. The result of this is that the teaching, assessing, and curriculum structure for engineering courses are set up using past experience and are not based on any solid foundation. Again, this is an added potential explanation for the high failure rate in engineering.